NLRC3 expression in dendritic cells attenuates CD4+ T cell response and autoimmunity. (10th July 2019) - Fu, Yuling; Zhan, Xiaoxia; Wang, Yichong; Jiang, Xiaobing; Liu, Min; Yang, Yalong; Huang, Yulan; Du, Xialin; Zhong, Xiao‐Ping; Li, Laisheng; Ma, Li; Hu, Shengfeng
Abstract: NOD‐like receptor (NLR) family CARD domain containing 3 (NLRC3), an intracellular member of NLR family, is a negative regulator of inflammatory signaling pathways in innate and adaptive immune cells. Previous reports have shown that NLRC3 is expressed in dendritic cells (DCs). However, the role of NLRC3 in DC activation and immunogenicity is unclear. In the present study, we find that NLRC3 attenuates the antigen‐presenting function of DCs and their ability to activate and polarize CD4 + T cells into Th1 and Th17 subsets. Loss of NLRC3 promotes pathogenic Th1 and Th17 responses and enhanced experimental autoimmune encephalomyelitis (EAE) development. NLRC3 negatively regulates the antigen‐presenting function of DCs via p38 signaling pathway. Vaccination with NLRC3‐overexpressed DCs reduces EAE progression. Our findings support that NLRC3 serves as a potential target for treating adaptive immune responses driving multiple sclerosis and other autoimmune disorders. Synopsis: The innate immune sensor NLRC3 negatively regulates dendritic cell activation to affect Th1 and Th17 cell differentiation and experimental autoimmune encephalomyelitis. NLRC3 attenuates the antigen‐presenting function of DCs and their ability to activate and polarize CD4 + T cells into Th1 and Th17 subsets. Loss of NLRC3 promotes pathogenic Th1 and Th17 responses and enhanced EAE development. NLRC3 negatively regulates the antigen‐presenting function of DCs via p38 signaling pathway. Abstract : The innate immune sensor NLRC3 negatively regulates dendritic cell activation to affect Th1 and Th17 cell differentiation and experimental autoimmune encephalomyelitis.